2016
DOI: 10.5897/ajar2016.11310
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of levels and determinants of technical efficiency of wheat producing farmers in Ethiopia

Abstract: Wheat is one of the most important cereal crops in Ethiopia, ranking fourth in total cereals production (16%) next to maize, sorghum and teff. Despite its potential for wheat grain production, Ethiopia falls short of being self-sufficient in wheat, and is currently a net importer of wheat grain. This study examines levels of and determinants of technical efficiency of wheat producing farmers in Ethiopia. Data was collected from 2017 farm households from the four major wheat growing regions of Ethiopia where ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 9 publications
(7 reference statements)
2
5
0
1
Order By: Relevance
“…This result is congruent with the study by Hailu (2008) and Asfaw et al (2012). Similarly, Hagos (2016) and Kaleb and Workneh (2016) found a positive influence of age on agricultural technology adoption in general. On the other hand, Bingxin et al (2011), Asfaw et al (2011), Hailu et al (2014 and Jaleta et al (2015) found a negative influence of age on adoption of technology confirming the younger age groups are adopters compared to their counterpart, the elders.…”
Section: Econometric Results Determinants For Adoption Of Technology supporting
confidence: 83%
“…This result is congruent with the study by Hailu (2008) and Asfaw et al (2012). Similarly, Hagos (2016) and Kaleb and Workneh (2016) found a positive influence of age on agricultural technology adoption in general. On the other hand, Bingxin et al (2011), Asfaw et al (2011), Hailu et al (2014 and Jaleta et al (2015) found a negative influence of age on adoption of technology confirming the younger age groups are adopters compared to their counterpart, the elders.…”
Section: Econometric Results Determinants For Adoption Of Technology supporting
confidence: 83%
“…Hypothesis tests that cannot be applied in nonparametric models, are possible in stochastic production frontier model. Different hypothesis tests were made for this study by using the likelihood ratio (LR) test given by Equation (11) following Greene (2003).…”
Section: Determinants Of Efficiencymentioning
confidence: 99%
“…Hence, improvement in the level of efficiency will increase productivity by enabling farmers to produce the maximum possible output from a given level of inputs with the existing level of technology Many researchers, in different sectors, have done many efficiency estimation studies in Ethiopia. However, the majority of farm efficiency studies are limited to technical efficiency (Fekadu and Bezabih, 2008;Yami et al, 2013;Beshir, 2016;Kelemu and Negatu, 2016;Assefa, 2016;Tiruneh and Geta, 2016). But, focusing only on technical efficiency (TE) understates the benefits that could be derived by producers from improvements in overall performance.…”
Section: Introductionmentioning
confidence: 99%
“…Eventually, it is predicted that the use of mobile phones will impact the behavior pattern of farmers, facilitating the adoption of improved practices leading to higher yields [33]. While a few recent studies [26,34] have conceptually discussed how mobile phones could translate to higher crop productivity, empirical evidence is scarce.…”
Section: Introductionmentioning
confidence: 99%